Early Hebrew Writing - Diringer, D.
Literary Sources — Paucity of Hebrew Inscriptions — Early Hebrew Inscriptions. Script and Language — Origin of the Early Hebrew Script — Early Hebr. Epigraphy. Development of Early Hebr. Writing — End of Early Hebr. Writing — Styles of Early Hebr. Writing — Early Hebr. Monumental or Lapidary Style of Writing — Early Hebr. Current Hand — Early Hebr. Book-Hand.